Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To determine the correct equation for [tex]\( p(x) \)[/tex] that fits the given data points [tex]\((-1, 10), (0, 1), (1, -2), (2, 1), (3, 10), (4, 25), (5, 46)\)[/tex], we will verify each of the provided equations by substituting the given [tex]\( x \)[/tex]-values and checking if the equation produces the corresponding [tex]\( p(x) \)[/tex]-values.
Given equations:
1. [tex]\( p(x) = 2(x-1)^2 - 2 \)[/tex]
2. [tex]\( p(x) = 2(x+1)^2 - 2 \)[/tex]
3. [tex]\( p(x) = 3(x-1)^2 - 2 \)[/tex]
4. [tex]\( p(x) = 3(x+1)^2 - 2 \)[/tex]
We need to find out which of these equations produces the correct [tex]\( p(x) \)[/tex] values for all given [tex]\( x \)[/tex]-values.
Firstly, let's try the equation [tex]\( p(x) = 3(x-1)^2 - 2 \)[/tex]:
For [tex]\( x = -1 \)[/tex]:
[tex]\[ p(-1) = 3(-1-1)^2 - 2 = 3(-2)^2 - 2 = 3 \cdot 4 - 2 = 12 - 2 = 10 \][/tex]
[tex]\( p(-1) = 10 \)[/tex] which matches the table.
For [tex]\( x = 0 \)[/tex]:
[tex]\[ p(0) = 3(0-1)^2 - 2 = 3(-1)^2 - 2 = 3 \cdot 1 - 2 = 3 - 2 = 1 \][/tex]
[tex]\( p(0) = 1 \)[/tex] which matches the table.
For [tex]\( x = 1 \)[/tex]:
[tex]\[ p(1) = 3(1-1)^2 - 2 = 3(0)^2 - 2 = 3 \cdot 0 - 2 = 0 - 2 = -2 \][/tex]
[tex]\( p(1) = -2 \)[/tex] which matches the table.
For [tex]\( x = 2 \)[/tex]:
[tex]\[ p(2) = 3(2-1)^2 - 2 = 3(1)^2 - 2 = 3 \cdot 1 - 2 = 3 - 2 = 1 \][/tex]
[tex]\( p(2) = 1 \)[/tex] which matches the table.
For [tex]\( x = 3 \)[/tex]:
[tex]\[ p(3) = 3(3-1)^2 - 2 = 3(2)^2 - 2 = 3 \cdot 4 - 2 = 12 - 2 = 10 \][/tex]
[tex]\( p(3) = 10 \)[/tex] which matches the table.
For [tex]\( x = 4 \)[/tex]:
[tex]\[ p(4) = 3(4-1)^2 - 2 = 3(3)^2 - 2 = 3 \cdot 9 - 2 = 27 - 2 = 25 \][/tex]
[tex]\( p(4) = 25 \)[/tex] which matches the table.
For [tex]\( x = 5 \)[/tex]:
[tex]\[ p(5) = 3(5-1)^2 - 2 = 3(4)^2 - 2 = 3 \cdot 16 - 2 = 48 - 2 = 46 \][/tex]
[tex]\( p(5) = 46 \)[/tex] which matches the table.
Since the function [tex]\( p(x) = 3(x-1)^2 - 2 \)[/tex] produces the correct [tex]\( p(x) \)[/tex] values for all given [tex]\( x \)[/tex]-values, the equation of [tex]\( p(x) \)[/tex] in vertex form is:
[tex]\[ p(x) = 3(x-1)^2 - 2 \][/tex]
Given equations:
1. [tex]\( p(x) = 2(x-1)^2 - 2 \)[/tex]
2. [tex]\( p(x) = 2(x+1)^2 - 2 \)[/tex]
3. [tex]\( p(x) = 3(x-1)^2 - 2 \)[/tex]
4. [tex]\( p(x) = 3(x+1)^2 - 2 \)[/tex]
We need to find out which of these equations produces the correct [tex]\( p(x) \)[/tex] values for all given [tex]\( x \)[/tex]-values.
Firstly, let's try the equation [tex]\( p(x) = 3(x-1)^2 - 2 \)[/tex]:
For [tex]\( x = -1 \)[/tex]:
[tex]\[ p(-1) = 3(-1-1)^2 - 2 = 3(-2)^2 - 2 = 3 \cdot 4 - 2 = 12 - 2 = 10 \][/tex]
[tex]\( p(-1) = 10 \)[/tex] which matches the table.
For [tex]\( x = 0 \)[/tex]:
[tex]\[ p(0) = 3(0-1)^2 - 2 = 3(-1)^2 - 2 = 3 \cdot 1 - 2 = 3 - 2 = 1 \][/tex]
[tex]\( p(0) = 1 \)[/tex] which matches the table.
For [tex]\( x = 1 \)[/tex]:
[tex]\[ p(1) = 3(1-1)^2 - 2 = 3(0)^2 - 2 = 3 \cdot 0 - 2 = 0 - 2 = -2 \][/tex]
[tex]\( p(1) = -2 \)[/tex] which matches the table.
For [tex]\( x = 2 \)[/tex]:
[tex]\[ p(2) = 3(2-1)^2 - 2 = 3(1)^2 - 2 = 3 \cdot 1 - 2 = 3 - 2 = 1 \][/tex]
[tex]\( p(2) = 1 \)[/tex] which matches the table.
For [tex]\( x = 3 \)[/tex]:
[tex]\[ p(3) = 3(3-1)^2 - 2 = 3(2)^2 - 2 = 3 \cdot 4 - 2 = 12 - 2 = 10 \][/tex]
[tex]\( p(3) = 10 \)[/tex] which matches the table.
For [tex]\( x = 4 \)[/tex]:
[tex]\[ p(4) = 3(4-1)^2 - 2 = 3(3)^2 - 2 = 3 \cdot 9 - 2 = 27 - 2 = 25 \][/tex]
[tex]\( p(4) = 25 \)[/tex] which matches the table.
For [tex]\( x = 5 \)[/tex]:
[tex]\[ p(5) = 3(5-1)^2 - 2 = 3(4)^2 - 2 = 3 \cdot 16 - 2 = 48 - 2 = 46 \][/tex]
[tex]\( p(5) = 46 \)[/tex] which matches the table.
Since the function [tex]\( p(x) = 3(x-1)^2 - 2 \)[/tex] produces the correct [tex]\( p(x) \)[/tex] values for all given [tex]\( x \)[/tex]-values, the equation of [tex]\( p(x) \)[/tex] in vertex form is:
[tex]\[ p(x) = 3(x-1)^2 - 2 \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.